LEVERAGING ARTIFICIAL INTELLIGENCE TO OPTIMIZE ENTERPRISE BUSINESS PROCESSES IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Єршова, Олена О. (Journal of Strategic Economic Research, 2025)
This article analyzes the theoretical and practical aspects of applying artificial intelligence (AI) to optimize business processes within the context of corporate sustainable development. It is demonstrated that amidst global environmental and social challenges, traditional management approaches are insufficient, and AI integration serves as a strategic lever for harmonizing economic, environmental and social imperatives. The essence of key definitions – "business process", "sustainable development", "corporate sustainability" and "artificial intelligence" – has been investigated. The fundamental principles of sustainable development and the key attributes of corporate sustainability are identified. The role and significance of business process management are elaborated upon. Seven key vectors of AI application that enhance operational efficiency and contribute to sustainable development goals are substantiated and systematized. These include: intelligent process automation, predictive analytics for decision support, optimization of logistics and supply chains, hyper-personalization of customer interaction, proactive risk management, intelligent manufacturing and the use of generative artificial intelligence to accelerate innovation. At the same time, the main advantages of introducing artificial intelligence (economic growth, promotion of public welfare, the concept of "Green AI") and systemic risks, including significant financial barriers, threats to data privacy, socio-ethical dilemmas related to algorithmic bias, and regulatory uncertainty, are investigated. It is argued that AI is a powerful catalyst for achieving operational excellence and long-term competitiveness; however, its successful implementation requires a clear strategy and an ethical approach to governance.